Beekeeping and Capacity Building for Sustainable Development: A Critical Assessment of a Beekeeping Training Programme in Cape Town’s Manenberg Township - Musaya, Lilly (Department of Social Development, 2019)
Beekeeping is an important industry in South Africa yet it is in decline. The South African government and development agencies see the increasing production deficits in the industry as a business opportunity for income generation for social-economically disadvantaged groups. However, most of these developmental initiatives, which have taken the form of beekeeping training programmes have not succeeded in creating a profitable and sustainable source of income. My study interrogated one such project in order to determine how beekeeping training programmes could be revised to increase the likelihood of trainees becoming viable beekeepers. I have drawn on the International Labour Organisation’s knowledge and skills development framework (called Training for Rural Economic Empowerment) to assess the methodological processes used in the development and implementation of the beekeeping programme. I collected data using a combination of qualitative interviews, documentary sources and participant observation, and then used Miles and Huberman’s thematic coding approach to analyse the qualitative data. My main finding is that there were methodological gaps in the pre-training, training and post-training phases of the beekeeping programme, either because of the exclusion of participants’/targeted groups’ inputs in the processes, or because participatory decision-making processes with participants were misapplied. As a result, the beekeeping training programme did not match the participants’ needs, economic opportunities in their area, and their social situations, and these circumstances contributed, in large part, to the graduates not taking up beekeeping.